ANALISIS EFEKTIVITAS PENJAMINAN KREDIT USAHA RAKYAT PADA PERUM JAMKRINDO KANTOR CABANG MANADO - Umboh, Timoty Erlan Kenny; Nangoi, Grace B.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Improving the performance of UMKM is faced by various obstacles and challenges on the competition. Lack of capital owned by UMKM entrepreneurs is a challenges at this time.Â  UMKM entrepreneurs are difficult to obtain loan capital because they don't have enough assets to complete the requirements of bank loans. To solve this problem, the government issued a policy credit program for UMKM with loans named People Business Credit Programs. This study aims to observe the Effectiveness of Credit Guarantee Effort of Public Enterprises at General Company Credit Guarantee Indonesia (Jamkrindo) Manado Branch Office. This research was conducted in Manado City with data taken from Public Credit Guarantee Company of Indonesia (Jamkrindo) Manado Branch Office using Qualitative research method and research method used by interview. The results of this study show that the Effectiveness Credit Guarantee Effectiveness Criteria in Manado has been running Effectively with the Effectiveness criteria in 2015 is 94.02% then in 2016 reached 95.87% and in 2017 reached 93.93%.Keywords : Effectiveness, Credit Guarantee, People Business Credits, UMKM